Lithospheric deformation in the Africa‐Iberia plate boundary: Improved neotectonic modeling testing a basal‐driven Alboran plate. Issue 9 (17th September 2016) - Neres, M.; Carafa, M. M. C.; Fernandes, R. M. S.; Matias, L.; Duarte, J. C.; Barba, S.; Terrinha, P.
Abstract: We present an improved neotectonic numerical model of the complex NW Africa‐SW Eurasia plate boundary segment that runs from west to east along the Gloria Fault up to the northern Algerian margin. We model the surface velocity field and the ongoing lithospheric deformation using the most recent version of the thin‐shell code SHELLS and updated lithospheric model and fault map of the region. To check the presence versus the absence of an independently driven Alboran domain, we develop two alternative plate models: one does not include an Alboran plate; another includes it and determines the basal shear tractions necessary to drive it with known velocities. We also compare two alternative sets of Africa‐Eurasia velocity boundary conditions, corresponding to geodetic and geological‐scale averages of plate motion. Finally, we perform an extensive parametric study of fault friction coefficient, trench resistance, and velocities imposed in Alboran nodes. The final run comprises 5240 experiments, each scored to geodetic velocities (estimated for 250 stations and here provided), stress direction data, and seismic strain rates. The model with the least discrepancy to the data includes the Alboran plate driven by a basal WSW directed shear traction, slightly oblique to the westward direction of Alboran motion. We provide estimates of long‐term strain rates and slip rates for the modeled faults, which can be useful for further hazard studies. Our results support that a mechanism additional to the Africa‐Eurasia convergence is required to drive the Alboran domain, which can be related to subduction processes occurring within the mantle. Key Points: Long‐term velocity field, deformation, and fault slip rates are modeled for Africa‐Iberia plate boundary Preferred scenario among several includes a third Alboran plate and AF‐EU motion defined by geodetic velocity model Alboran is driven by slab‐related basal mechanisms, and slab dynamics has effects on lithospheric processes